Participatory journalism in Africa digital news engagement and user agency in the south - Mabweazara, Hayes Mawindi 1977-; Mare, Admire (Disruptions: studies in digital journalism, 2021)
This book offers an African perspective on how news organisations are embracing digital participatory practices as part of their everyday news production, dissemination and audience engagement strategies. Drawing on empirical evidence from news organisations in sub-Saharan Africa, Participatory Journalism in Africa investigates and maps out professional practices emerging with journalists' direct interactions with readers and sources via online user comment spaces and social media platforms. Using a social constructivist approach, the book focuses on the challenges relating to the elite-centric nature of active participation on the platforms, while also highlighting emerging ethical and normative dilemmas. The authors also point to the hidden structural controls to participation and user engagement associated with artificial intelligence, chatbots and algorithms. These obstacles, coupled with low digital literacy levels and the well-established pitfalls of the digital divide, challenge the utopian view that in Africa interactive digital technologies are the sine qua non spaces for democratic participation. This is a valuable resource for academics, journalists and students across a wide range of disciplines including journalism studies, communication, sociology and political science